Pengaruh taburia terhadap status anemia dan status gizi balita gizi kurang - Wahyuni Kunayarti; Madarina Julia; Joko Susilo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Micronutrient deficiency seriously contributes to child morbidity and mortality. The need for micronutrient can be fulfilled from food, fortified food, and direct supplementation. Taburia is multivitamin multimineral that is aimed to meet the need for micronutrient of undernourished under-fives and to prevent the increased prevalence of undernourishment. It is necessary efficacy and effectiveness study of Taburia to anemia and nutritional status of undernourished under fives of 24-55 months.Objective: To identify the effect of Taburia supplementation to anemia and nutrition status of under fives at District of Lombok Timur.Method: The study was experimental with prospective cohort study design carried out at District of Lombok Timur, Province of Nusa Tenggara Barat. The subject of the study was undernourished under fives at the area of Nutrition Improvement Community through Empowerment (NICE) project. The independent variables were Taburia and biscuits; the dependent variables were anemia and nutrition status; and the external variables were the intake of energy, protein, vitamin A, vitamin C, Fe, and zinc. Data analysis used ANOVA and paired t-test.Results: There was a significant difference in the average level of hemoglobin of the subject after the intervention, either in taburia group, biscuit group, or taburia+biscuit group (p<0.05). There was the difference in average weight after intervention in the three groups (p<0.05). There was no significant difference in the average level of hemoglobin and the average level of weight between biscuit group and Taburia+biscuit group. There was a change in anemia status from anemia to nonanemia; the highest was in Taburia group, i.e. 96%; and better nutrition status at the end of the experiment occurred at Taburia+biscuit group from emaciated to normal (100%).Conclusion: Taburia supplementation could increase anemia status. Micronutrient supplementation was needed to increase nutrition status.